Optimizing international class program diversification through digital technology at the Islamic junior high school in Malang, Indonesia - Fantika Febry Puspitasari; Supriyanto Supriyanto (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2023)
Â Through the International Class Program (ICP), SMP Muhammadiyah 2 Inovasi Malang facilitates active English learning. Active English learning necessitates consistent actualization practice activities. Schools are expected to maximize the use of online media for educational purposes. This research explores technology-based ICP activities and the media used to optimize ICP program collaboration. This study employs a qualitative research method based on case studies; the data are presented descriptively. The investigation was conducted over the course of six months, from June to November of 2022. Several key informants, including principals, program coordinators, and program participants/students, were interviewed to collect data; they were assigned as research subjects. Additionally, researchers performed field observations and documentation. Data analysis techniques include data reduction, data presentation, and conclusions. The findings indicated that SMP Muhammadiyah 2 Inovasi Malang could take advantage of the Covid-19 pandemic by optimizing online media, such as virtual meetings in the ICP class. Instagram, YouTube, and video production are other media. Another finding is that space, time, and financial constraints can be effectively managed. Differentiated learning requires intensive assistance from Kampung Inggris supplemented by International Student Discussions and project-based learning. Nevertheless, this program must still surmount two obstacles: the low level of student self-confidence and the diversity of student abilities.